Relationship between the molecular structure of duckweed starch and its in vitro enzymatic degradation kinetics - de Souza Moretti, Marcia Maria [UNESP]; Yu, Wenwen; Zou, Wei; Franco, Célia Maria Landi [UNESP]; Albertin, Liliane Lazzari [UNESP]; Schenk, Peer M.; Gilbert, Robert G. (Elsevier, 2019)
Starch molecular structural effects in duckweed (Lemna minor and Landoltia punctata) controlling in vitro enzymatic degradation kinetics was studied. The molecular size distributions of fully-branched starches and the chain length distributions (CLDs) of enzymatically debranched duckweed starches were obtained using size-exclusion-chromatography (SEC). The CLDs of both debranched amylose and amylopectin were fitted with models using biologically-meaningful parameters. While there were no significant correlations between amylose content and starch degradation rate, the total amounts of amylose with shorter chain length negatively correlated with undigested starch content, and the amount of amylopectin long chains negatively correlated with the degradation rate coefficient. This provides new knowledge for the utilization of duckweed starches in bioethanol production.
Keywords: Duckweed; Molecular structure; Size-exclusion chromatography (SEC); Starch; Starch degradation